Editorial - Bhattarai, S (Nepal Journal of Dermatology, Venereology & Leprology, 2016)
<!–[if gte mso 9]> <![endif]–> No abstract available. DOI: http://dx.doi.org/10.3126/njdvl.v12i1.10587 Nepal Journal of Dermatology, Venereology & Leprology Vol.12(1) 2014, page i <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:8.0pt; mso-para-margin-left:0in; line-height:107%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; –> <!–[endif] –>